ANALISIS PERBANDINGAN METODE FUZZY MFEP DAN FUZZY SAW UNTUK PEMILIHAN SUSU FORMULA - Hendrawan, Satya Arisena; Saptoto, Robertus; Yazid , Ahmad (STMIK BINA PATRIA, 2026)
Selecting the appropriate milk product is essential to fulfill nutritional needs. The wide variety of milk products available in the market, with differences in nutritional content, price, and taste, often makes it difficult for consumers to make optimal decisions. This study aims to analyze and compare the Fuzzy Multi Factor Evaluation Process (Fuzzy MFEP) and Simple Additive Weighting (SAW) methods in determining the best milk product based on several criteria, including protein content, price, expiration period, taste/variant, and sugar content. This research applies a Multiple Criteria Decision Making (MCDM) approach, where each alternative is evaluated using predefined criteria weights. The results show that the SAW method identifies Greenfields as the best alternative with the highest preference value, while the Fuzzy MFEP method ranks Indomilk as the top alternative. This difference occurs due to the distinct characteristics of each method, where Fuzzy MFEP emphasizes subjective evaluation, while SAW relies on structured numerical data. Further analysis indicates that the SAW method is more consistent and efficient for quantitative data processing in consumer product selection. Therefore, SAW is recommended as a more effective decision support method in this context. This study contributes to providing a rational and data-driven approach for consumers in selecting milk products. Keywords: Decision Support System, MCDM, SAW, Fuzzy MFEP, milk